Randomised controlled trial of a video intervention and behaviour contract to improve medication adherence after renal transplantation: the VECTOR study protocol. Issue 3 (13th March 2019) - Mansell, Holly; Rosaasen, Nicola; West-Thielke, Patricia; Wichart, Jenny; Daley, Christopher; Mainra, Rahul; Shoker, Ahmed; Liu, Juxin; Blackburn, David
Abstract : Introduction: Non-adherence after kidney transplantation contributes to increased rejections, hospitalisations and healthcare expenditures. Although effective adherence interventions are sorely needed, increasing education and support to transplant recipients demands greater use of care providers' time and resources in a healthcare system that is stretched. The objective of this clinical trial is to determine the effectiveness of an electronically delivered video series and adherence behaviour contract on improving medication adherence to immunosuppressant medications. Methods and analysis: A multicentre, parallel arm, randomised controlled trial will be conducted with four sites across North America (Saskatoon, Calgary, Halifax, Chicago). Adult patients will be randomised (1:1) to either the intervention (ie, home-based video education +behaviour contract plus usual care) or usual care alone. De novo transplant recipients will be enrolled prior to their hospital discharge and will be provided with electronic access to the video intervention (immediately) and adherence contract (1 month post-transplant). Follow-up electronic surveys will be provided at 3 and 12 months postenrolment. The primary outcome will be adherence at 12 months post-transplant, as measured by self-report Basel Assessment of Adherence to Immunosuppressive medications and immunosuppressant levels. Secondary outcomes include the difference in knowledge score between the intervention and control in groups (measured by the Kidney Transplant Understanding Tool); differences in self-efficacy (Generalised Self-efficacy Scale), Beliefs of Medicine Questionnaire (BMQ), quality of life (Short Form-12), patient satisfaction and cost utilisation. The study aims to recruit at least 200 participants across participating sites. Ethics and dissemination: Ethical approval was obtained from the University of Saskatchewan Behavioural Ethics Committee (Beh 18–63), and all patients provide informed consent prior to participating. This educational intervention aims to improve information retention and self-efficacy, leading to improved medication adherence after kidney transplantation, at low cost, with little impact to existing healthcare personnel. If proven beneficial, delivery can be easily implemented into standard of care. Trial registration number: NCT03540121 ; Pre-results.